2021
DOI: 10.1177/15459683211011214
|View full text |Cite
|
Sign up to set email alerts
|

A New Definition of Poststroke Spasticity and the Interference of Spasticity With Motor Recovery From Acute to Chronic Stages

Abstract: The relationship of poststroke spasticity and motor recovery can be confusing. “True” motor recovery refers to return of motor behaviors to prestroke state with the same end-effectors and temporo-spatial pattern. This requires neural recovery and repair, and presumably occurs mainly in the acute and subacute stages. However, according to the International Classification of Functioning, Disability and Health, motor recovery after stroke is also defined as “improvement in performance of functional tasks,” i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 84 publications
0
88
0
5
Order By: Relevance
“…Secondary to damage to the motor cortex and/or to the corticobulbar pathways after stroke, excitability of the contralateral medial cortico-reticulo-spinal pathways becomes unopposed and gradually upregulated, thus resulting in un-opposed excitatory inputs to spinal reflex circuits [5][6][7]. In the presence of externally imposed muscle stretch, the phenomenon of velocity-dependent stretch reflex responses, i.e., spasticity, is manifested [8,9]. On the other hand, this pathophysiological process of hyperexcitable descending brainstem pathways is shared by other motor impairments, e.g., inappropriate muscle activation [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary to damage to the motor cortex and/or to the corticobulbar pathways after stroke, excitability of the contralateral medial cortico-reticulo-spinal pathways becomes unopposed and gradually upregulated, thus resulting in un-opposed excitatory inputs to spinal reflex circuits [5][6][7]. In the presence of externally imposed muscle stretch, the phenomenon of velocity-dependent stretch reflex responses, i.e., spasticity, is manifested [8,9]. On the other hand, this pathophysiological process of hyperexcitable descending brainstem pathways is shared by other motor impairments, e.g., inappropriate muscle activation [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of externally imposed muscle stretch, the phenomenon of velocity-dependent stretch reflex responses, i.e., spasticity, is manifested [8,9]. On the other hand, this pathophysiological process of hyperexcitable descending brainstem pathways is shared by other motor impairments, e.g., inappropriate muscle activation [7,9]. During sustained voluntary elbow flexion on the spastic-paretic side of stroke survivors, Rymer and colleagues have reported that spinal motor neurons are hyperexcitable and even spontaneously firing.…”
Section: Introductionmentioning
confidence: 99%
“…Spasticity and muscle weakness on the affected side (i.e., hemiparesis) are two hallmark motor impairments after stroke. Recent advances have shown that these two motor impairments are mediated by distinctly different pathophysiological mechanisms (1)(2)(3)(4). Hemiparesis, as a result of damage of motor cortex and/or its descending corticospinal tracts, occurs immediately after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al extended velocity dependence to position as well as velocity dependence ( 4 ). Li et al extended velocity dependence to velocity as well as muscle length-dependent increase in resistance ( 5 ). It results from hyperexcitable descending excitatory brainstem pathways and the resultant exaggerated stretch reflex responses.…”
Section: Introductionmentioning
confidence: 99%
“…It results from hyperexcitable descending excitatory brainstem pathways and the resultant exaggerated stretch reflex responses. Other related motor impairments, including abnormal synergies, inappropriate muscle activation, and anomalous muscle coactivation, coexist with spasticity and share similar pathophysiological origins ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%